2022
DOI: 10.1039/d2cc00473a
|View full text |Cite
|
Sign up to set email alerts
|

Heterometallic uranium/molybdenum nitride synthesis via partial N-atom transfer

Abstract: The reaction of a terminal Mo(II) nitride with a U(III) complex yields an heterodimetallic U-Mo nitride which is the first example of a transition metal-capped uranium nitride. The nitride is...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…The few multimetallic uranium–alkali ion systems reported so far that effect the four-electron reduction of N 2 , 1 j , m ,3 h or even its complete cleavage to nitride, 4 all contain the potassium cation. It should be noted that although the number of reported uranium nitride complexes is rapidly increasing 12,13 only three examples of uranium nitrides have been obtained from N 2 reduction (Chart 1).…”
Section: Introductionmentioning
confidence: 99%
“…The few multimetallic uranium–alkali ion systems reported so far that effect the four-electron reduction of N 2 , 1 j , m ,3 h or even its complete cleavage to nitride, 4 all contain the potassium cation. It should be noted that although the number of reported uranium nitride complexes is rapidly increasing 12,13 only three examples of uranium nitrides have been obtained from N 2 reduction (Chart 1).…”
Section: Introductionmentioning
confidence: 99%
“…In 2022, Mazzanti, Agapie, and co-workers reported the first example of a heterometallic uranium-transition metal nitride complex, [Na(U(OSi(O t Bu) 3 (μ-N)(MoP 2 ))] (70) (P 2 = terphenyl diphosphine ligand), generated from partial N-transfer to the U( iii ) precursor, [U III (OSi(O t Bu) 3 ) 3 (THF) 2 ], from the Na-capped molybdenum( ii ) nitride, [Na(N)Mo II P 2 ] (70a) ( Scheme 14a ). 117 The solid-state molecular structure of 70 displays a U–Mo heterometallic complex bridged by a N 3− ligand, where the U and Mo centers are in close proximity with a U–Mo distance of 3.1032(2), which was slightly shorter than the distances found in other heterometallic U–Mo complexes bridged by phosphinoamide ligands (3.1682(4), 3.159(2) Å). 118 The short U–Mo bond distance highlights the ability of the bridging nitride and bridging arene of the P 2 ligand in 70 to promote metal–metal interactions.…”
Section: Heterometallic Actinide/transition Metal Nitride Complexesmentioning
confidence: 92%
“…resulted in the reductive carbonylation of the nitride, leading to the formation of NaN13CO (10–50% yield) and the previously reported Mo(0) carbonyl complexes, [P 2 Mo 0 ( 13 CO)] or [P 2 Mo 0 ( 13 CO) 3 ] (in low yield), as well as multiple unidentified diamagnetic species ( Scheme 16b ). 117 The uranium species formed in the reaction could not be identified, but the formation of NaN 13 CO was unambiguously demonstrated by 13 C NMR spectroscopy of the reaction mixture in D 2 O. The reductive carbonylation of the U( v ) nitride most likely proceeds with release of the Mo(0) complex, but reactivity with complex 70 was not ruled out.…”
Section: Reactivity Of Actinide Nitride Complexesmentioning
confidence: 96%
“…This work provides a useful strategy for promoting productive group transfer reactivity in stable early transition-metal nitrides. Recently, Mazzanti, Maron, and Agapie showed that the nitride ligand in Na[ 1008 ] is partially transferred to the uranium(III) precursor [U(OSi t Bu 3 ) 3 ­(thf) 2 ] ( 1012 ), affording the first example of a transition metal-capped uranium nitride Na[U(OSi t Bu 3 ) 3 ­(μ-N)Mo(tpdp)] ( 1013 ) . The experimental and computational data point to an N -transfer accompanied by a two-electron transfer from uranium to molybdenum, formally resulting in the nitride triply bonded to U(V) and singly bonded to Mo(0).…”
Section: Metalates In Small-molecule Activation and Catalysismentioning
confidence: 99%